Alcohol Risk Management in College Settings: The Safer California Universities Randomized Trial - Saltz, Robert F. (2010)
CONTEXT: Potentially effective environmental strategies have been recommended to reduce heavy alcohol use among college students. However, studies to date on environmental prevention strategies are few in number and have been limited by their non-experimental designs, inadequate sample sizes, and lack of attention to settings where the majority of heavy drinking events occur. PURPOSE: To determine whether environmental prevention strategies targeting off-campus settings would reduce the likelihood and incidence of student intoxication at those settings. DESIGN: The Safer California Universities study involved 14 large public universities, half of which were randomly assigned to the Safer intervention condition after baseline data collection in 2003. Environmental interventions took place in 2005 and 2006 after 1 year of planning with 7 Safer intervention universities. Random cross-sectional samples of undergraduates completed online surveys in four consecutive fall semesters (2003–2006). SETTING/PARTICIPANTS: Campuses and communities surrounding 8 campuses of the University of California and 6 in the California State University system were utilized. The study used random samples of undergraduates (~500–1,000 per campus per year) attending the 14 public California universities. INTERVENTION: Safer environmental interventions included nuisance party enforcement operations, minor decoy operations, DUI checkpoints, social host ordinances, and use of campus and local media to increase the visibility of environmental strategies. MAIN OUTCOME MEASURES: Proportion of drinking occasions in which students drank to intoxication at six different settings during the fall semester (residence hall party, campus event, fraternity or sorority party, party at off-campus apartment or house, bar/restaurant, outdoor setting), any intoxication at each setting during the semester, and whether students drank to intoxication the last time they went to each setting. RESULTS: Significant reductions in the incidence and likelihood of intoxication at off-campus parties and bars/restaurants were observed for Safer intervention universities compared to controls. A lower likelihood of intoxication was also observed for Safer intervention universities the last time students drank at an off-campus party (OR=0.81, 95% CI=0.68, 0.97), a bar or restaurant (OR=0.76, 95% CI=0.62, 0.94), or any setting (OR=0.80, 95% CI=0.65, 0.97). No increase in intoxication (e.g., displacement) appeared in other settings. Furthermore, stronger intervention effects were achieved at Safer universities with the highest level of implementation. CONCLUSIONS: Environmental prevention strategies targeting settings where the majority of heavy drinking events occur appear to be effective in reducing the incidence and likelihood of intoxication among college students.